Functionalisation of an organic-inorganic hybrid polyoxometalate with an organic chromophore - Feng, Zimou (2020)
It has been a long-sought scientific target for sustainable chemistry to make effective use of solar energy to drive reactions. Recent research is shining a light on molecular photocatalysts with versatility and tunable properties. Polyoxometalates (POMs) have shown great potential as a result of their appealing photo- and electrochemical properties, as well as their unmatched structural diversity, excellent stability and tunable solubility.